Pembentukan Buah dan Perkecambahan Tanaman Jarak Pagar pada Transformasi Langsung Melalui Jalur Tabung Polen - Zainudin, Agus; Purwoko, Bambang Sapta; Santoso, Tri Joko; Ardie, Sintho Wahyuning; Trikoesoemaningtyas, dan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
The genetic transformation via pollen-tube pathway in jatropha is the first alternative method that was applied in this plant. The objective of the research was to study fruit set and germination of three genotypes of jatropha following direct transformations via pollen-tube pathways. The research was conducted during April 2014 until January 2015 at jatropa’s experimental field, Pasuruan, and at green house of ICABIOGRAD, Bogor. Three genotypes of jatropha i.e., IP3A, IP3P and JcUMM18 were used. In the first experiment, split plot design was used where 3 levels of DNA plasmid concentration as a main plot and 5 levels of stigma-drip time of DNA plasmid as a subplot. In the second experiment randomized block design was used with single factor consisting of 15 combinations of concentration and stigma-drip time of DNA plasmid as treatments and control. The results demonstrated that interaction between concentration and application time of DNA plasmid did not significantly affect fruit and seeds formation of three Jatropha genotypes. Combination of DNA plasmid concentration with time of stigma-drip had significant effect on seed germination rate of IP3A genotype, but not significant on the other variables. The concentration of 0.05-0.5 µg µL-1 and application time of DNA plasmid at 1-10 hours after pollination could be applied on jatropha genetic transformation via pollen-tube pathways.Keywords: DNA plasmid, Jatropha curcas, pCAMBIA1301, pollen-tube, stigma-drip